Legal Protection Of Consumer Personal Data In Electronic Transactions With Legal Certainty - Sihite, Thomas Ericson Hadinata; Iryani, Dewi; Setiawan, Puguh Aji Hari (jurnal.unprimdn.ac.id, 2025)
Online buying and selling can result in the leakage of consumer personal data, as seen in the breaches of user accounts on the Tokopedia and Shopee marketplaces. The data leaks on e-commerce platforms have left users' personal data unprotected. Law No. 19 of 2016 also does not specifically address personal data protection. The type of research used in this research is normative legal research. The results of this research, namely Regulations related to the protection of personal data according to the laws and regulations in force in Indonesia, include: Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions is a revision of Government Regulation Number 82 of 2012. In addition, it is also regulated in Government Regulation No. 44 of 2008 concerning the Provision of Compensation, Restitution, and Assistance to Victim Witnesses, in addition there is Article 1 paragraph (6) and Article 5 paragraph (1) Point A of the Law concerning the Protection of Witnesses and Victims, PERKOMINFO (Regulation of the Minister of Communication and Information) Number 20 of 2016 and Article 28 paragraph (1) of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions. These regulations are aimed at encouraging the public to respect personal data, which is part of the right to privacy, so that other people's personal data is not widely disseminated or traded for any reason. Legal protection of consumer personal data in electronic transactions with legal certainty is as stated in Article 19 of the Consumer Protection Law, which states that e-commerce startups are responsible for losses experienced by consumers by providing administrative compensation to consumers.